Causes of Violence Against Women and Children Based On 7 (Seven) Root Causes of Violence According to Kauffman, 1999 & Nur Iman Subono, 2018 - Mariana Ngundju Awang; Wilhelmina Apriana Ariesta Woda; Diyan Maria Kristin (Green Publisher Indonesia, 2022)
The amount of violence against girls in recent years has always been the third highest. In the realm of domestic violence/personal relations, it presents that being a girl in the house is no longer a safe thing. They experience sexual violence. Percentage of Women Victims of Violence in NTT Province comprise of: persecution is 44.03%, humiliation is 65.01%, harassment is 7.12%, neglect is 12.71%, and others 13.02%. As much as 68.85% of perpetrators are parents and victims of violence against girls 1.91% in rural areas and 2.23 in urban areas. Research Objective: Identifying the Causes of Violence against Women and Children based on 7 (seven) Root Causes of Violence according to Kauffman, 1999 & Nur Iman Subono 2018. Research Method: The type of research is mixed method: qualitative and quantitative studies with descriptive research types. Informants are parents of married men and women aged <65 years with the sample criteria still being wife/husband, not widow/widower divorcing alive/dead, living together for more than 1 year. Girls and boys aged 18-25 years and unmarried, living with their parents. Conclusion: Most of the respondents stated that the reason why men commit violence is because of the dominant patriarch culture, masculinity, past experiences of violence and erreneous understanding of customs and religion & law enforcement which is not firm or unfair.